The Altruistic Behaviour of Consumers Who Prefer a Local Origin of Organic Food - Adam Czudec (Agriculture, 2022)
Despite the fact that consumer behaviour in the organic foods market has been the subject of numerous studies in various countries around the world, little research has been devoted to the assessment of the importance of the altruistic behaviour of consumers who prefer a local origin of such food. Therefore, the aim of this paper was to determine the motives of organic food consumers for their interest in the local origin of food in the context of behaviour defined as either altruistic or egoistic. The study was carried out among 850 consumers of organic foods in Poland. The Kruskal–Wallis test and Dunn’s post hoc test were used for the analysis of empirical data. This study shows that the emphasis on the importance of the local origin of this kind of food by organic food consumers is related to their awareness of the needs of other people; specifically, this is demonstrated by these consumers taking into account the importance of caring for the natural environment in their purchasing decisions. Therefore, this is an example of altruistic behaviour which also fits into the concept of reflexive localism. It was further determined that this consumer group has a stronger and more robust relationship with the organic food market than the market’s other members.